Minority Contracting and Affirmative Action for Disadvantaged Small Businesses : Legal Issues. (U.S. Congressional Research., 2006)
Discusses the ramifications of the application of "strict scrutiny" to race-conscious decision making by the Federal Government as established by the Supreme Court in Adarand Constructors, Inc. v. Pena. Reviews regulatory developments post- Adarand, implications for future minority contracting cases, and policy concerning affirmative action for disadvantaged small businesses.